The Role of Zakat in Realizing Sustainable Development Goals (SDGs) to Increase Community Economic Income (Study on Baitul Mal of Banda Aceh City) - Hafidhah, Hafidhah; Sari, Nilam; Wirda, Wirda (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
This study examines the Analysis of Mustahik Income Before and After receiving Productive Zakat from Baitul Mal in Banda Aceh City. Productive zakat plays an important role in increasing mustahik income. With the productive zakat program, it is very helpful for Mustahik in adding capital for business, building a business, developing a business, and and creating employment opportunities. This study aims to determine the role and implementation of zakat and analyze the differences in Mustahik income before and after the distribution of business capital assistance through productive zakat by Baitul Mal Kota Banda Aceh. This research is a Quantitative Research using the Wilcoxon Matched Pairs Test analysis method. The research sample used was 81 Mustahik productive zakat recipients using the Area Cluster Random Sampling technique. This study found that there were differences in Mustahik's income before and after receiving productive zakat, this shows that the provision of productive zakat in realizing SDGs has an important role in increasing the income of the community (Mustahik) implemented by Baitul Mal Kota Banda Aceh.